Pengembangan Media Pembelajaran X-Pirate Berbasis ICT Pada Materi Persamaan Linear Satu Variabel - Niken Ayu Paras Sari; Janet Trineke Manoy (MATHEdunesa, 2026)
This research aims to develop and test the feasibility of ICT-based X-Pirate learning media on Single Variable Linear Equations (SVLE) material to increase students' interest, motivation, and learning outcomes. The development used the ADDIE model with 29 eighth-grade students as subjects. The validation results showed that the X-Pirate media was highly valid, with a score of 98% from media experts and 90% from subject matter experts. The media was also considered highly practical, as evidenced by the 86.75% implementation rate, 80% teacher response rate, and 85% student response rate. The effectiveness of the media was demonstrated through improved learning outcomes with an N-Gain score of 0.46 in the moderate category. Overall, X-Pirate was declared valid, practical, and effective as ICT-based learning media for PLSV material.